Computed Tomography–Determined Body Composition Abnormalities Usefully Predict Long-term Mortality in Patients With Liver Cirrhosis. Issue 5 (September 2021) - Cho, Young Seo; Lee, Ha Young; Jeong, Jae Yoon; Lee, Jae Gon; Kim, Tae Yeob; Nam, Seong Woo; Sohn, Joo Hyun
Abstract : Objective: We evaluated the prognostic impacts of body composition components measured by computed tomography (CT) in patients with liver cirrhosis. Methods: A total of 160 cirrhotic patients who underwent CT and hepatic venous pressure gradient measurements were retrospectively enrolled. Cross-sectional areas of skeletal muscle, visceral and subcutaneous fat, and mean CT attenuation of trabecular bone of the fourth lumbar vertebral level (L4HU ) were measured. Results: Multivariate analysis showed model for end-stage liver disease score [hazard ratio (HR), 1.086; 95% confidence interval (CI), 1.020–1.156; P = 0.010], hepatic venous pressure gradient (HR, 1.076; 95% CI, 1.021–1.135; P = 0.006), sarcopenia (HR, 1.890; 95% CI, 1.032–3.462; P = 0.039), and L4HU (HR, 1.960 for L4HU <145 Hounsfield units; 95% CI, 1.094–3.512; P = 0.024) were independently associated with long-term mortality. In patients with decompensated cirrhosis, subcutaneous adipose tissue index was the only independent predictor (HR, 0.984; 95% CI, 0.969–0.999; P = 0.039). Conclusion: Body composition abnormalities determined by CT are associated with long-term prognosis in cirrhotic patients. Abstract : Supplemental digital content is available in the text.